ASSESSMENT OF YIELD CRITERIA IN BREAD WHEAT THROUGH CORRELATION AND PATH ANALYSIS - J. Anwar; M. A. Ali; M. Hussain; W. Sabir; M. A. Khan; M. Zulkiffal; M. Abdullah (Journal of Animal and Plant Sciences, 2009)
The study was conducted at wheat Research Institute, Faisalabad during 2006-2008. Significant genotypic differences were existed among the genotypes. Correlation coefficients were computed for grain yield plant-1, tillers plant-1, spikelets spike-1, 1000 grain weight, spike length, days to heading, days to maturity and plant height from the F1 crosses developed from four lines and three testers including their parents. The results revealed that grain yield plant-1 was positively and significantly correlated with number of tillers plant-1 and days to maturity at genotypic level but non-significantly correlated at phenotypic level. Days to maturity had positive genotypic correlation with grain yield plant-1, number of tillers plant-1 and 1000-grain weight. Days to maturity and tillers plant-1 had positive direct effect on grain yield plant-1 also. Therefore, more days to maturity and more tillers plant-1 would be important selection criteria for improved grain yield plant-1 in the breeding material studied.
Keywords: Bread wheat; yield criteria; characters associations; path analysis